2013
DOI: 10.3892/mco.2013.194
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of expression of transporters associated with antigen processing 1 and 2 and human leukocyte antigen I and its effect on immunity in nasopharyngeal carcinoma patients

Abstract: Abstract. The human leukocyte antigen (HLA)-I and antigen-processing machinery (APM) are crucial in the anticancer immune response. The aim of this study was to assess the clinical significance of the APM components [transporters associated with antigen processing (TAP)-1 and -2 and HLA-I] in nasopharyngeal carcinoma (NPC). A total of 58 NPC specimens and 20 healthy specimens used as control were evaluated by semiquantitative immunohistochemistry for three APM components (TAP-1, TAP-2 and HLA-I). The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These findings, bolstered by the observation that A * 0201 and A * 1101 mediate the strongest responses to CD8+ T cell epitopes in LMP2, suggest that virus-specific CD8+ T cell surveillance does play a protective role at some stage in the pathogenesis of these tumors (23). This is further supported by the fact that in up to 30% cases both EBV-positive HL (177) and NPC (178) appear to have either partially or completely lost HLA I expression, a finding which for NPC has recently been validated by genomic studies showing mutation of either individual HLA I alleles or pan-HLA pathway genes (142). Parallel studies that focus on the EBV-positive subset of gastric cancers are awaited with interest.…”
Section: The Search For Common Themes In Ebv-associated Oncogenesismentioning
confidence: 82%
“…These findings, bolstered by the observation that A * 0201 and A * 1101 mediate the strongest responses to CD8+ T cell epitopes in LMP2, suggest that virus-specific CD8+ T cell surveillance does play a protective role at some stage in the pathogenesis of these tumors (23). This is further supported by the fact that in up to 30% cases both EBV-positive HL (177) and NPC (178) appear to have either partially or completely lost HLA I expression, a finding which for NPC has recently been validated by genomic studies showing mutation of either individual HLA I alleles or pan-HLA pathway genes (142). Parallel studies that focus on the EBV-positive subset of gastric cancers are awaited with interest.…”
Section: The Search For Common Themes In Ebv-associated Oncogenesismentioning
confidence: 82%
“…There is less data on NPC, but it has been reported that complete loss of HLA class I expression occurs in approximately 20% of cases and partial loss in an additional 58% of cases [ 98 ]. Another study showed a loss of HLA class I expression in 50% of NPC cases [ 99 ]. Other changes in the antigen presenting machinery may alter the quality and quantity of presented peptides as well.…”
Section: Immune Escape Mechanismsmentioning
confidence: 99%
“…HLA-II is up regulated in EBVaGC, where EBNA2 is not typically expressed [69]. This is also different than the effects observed in an EBV+ nasopharyngeal carcinoma, where HLA class II expression is down iñ 50% of the cases [70,71]. Thus, EBNA2 down regulation of CIITA may be cell-type specific, depending on chromatin domain structure and enhancer wiring particular to B-cells but perhaps different in EBV epithelial cancers.…”
Section: Plos Pathogensmentioning
confidence: 81%